(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, congenital ichthyosis in children and its causes are analyzed in detail. Also, special attention is paid to the genetic basis of the disease, its types of inheritance (autosomal-dominant, autosomal-recessive and X-chromosomal forms) and clinical symptoms. The article discusses the main etiological factors of the disease, including gene mutations, adverse factors during prenatal development, and environmental influences. The importance of prenatal screening, ultrasound examination, assessment of clinical symptoms and laboratory studies as diagnostic methods is shown.